TINDAK TUTUR DIREKTIF PADA ANAK USIA 7-10 TAHUN DI GANG RAMBUTAN, KELURAHAN SINDANG MARGA, KECAMATAN PULAU PANGGUNG, KABUPATEN TANGGAMUS - Raissa Zahara, Sella; Saputry, Dessy; Fitriyani, Dwi (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2023)
The purpose of this research article is to describe types of directive speech acts and analyze the meaning in conversations of children aged 4-6 years in Gang Rambutan, Sindang Marga Village, Pulau Panggung District, Tanggamus Regency. The method used in this research is a descriptive method with a qualitative approach. The data source used in this research is speech data containing directive speech acts. Data collection techniques use observation, interview, recording, listening and note-taking techniques. Data were analyzed using pragmatic analysis. The results of the research show that in children's speech interactions in Gang Rambutan, Sindang Marga Village, Pulau Panggung District, Tanggamus Regency, there are four types of directive speech acts, namely directives inviting, requesting, pleading, and challenging.Â